2013
DOI: 10.1186/1477-7525-11-55
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of yoga as self-care for arthritis in minority communities

Abstract: BackgroundWhile arthritis is the most common cause of disability, non-Hispanic blacks and Hispanics experience worse arthritis impact despite having the same or lower prevalence of arthritis compared to non-Hispanic whites. People with arthritis who exercise regularly have less pain, more energy, and improved sleep, yet arthritis is one of the most common reasons for limiting physical activity. Mind-body interventions, such as yoga, that teach stress management along with physical activity may be well suited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 71 publications
(66 reference statements)
0
37
0
2
Order By: Relevance
“…O que pode ser explicado pelos benefĂ­cios ofertados pela atividade fĂ­sica regular para os indivĂ­duos com AR, como a redução da dor, a melhora das condiçÔes gerais de vida, da qualidade do sono, das condiçÔes energĂ©ticas e do desempenho funcional, especialmente a longo prazo. 22 Os resultados evidenciados neste estudo concordam com outros achados na literatura. Myra et al (2015) realizaram um estudo de caso com um indivĂ­duo do gĂȘnero feminino com AR associada ao lĂșpus eritematoso sistĂȘmico, onde o submeteram a 15 sessĂ”es de cinesioterapia, duas vezes por semana.…”
Section: Discussionunclassified
“…O que pode ser explicado pelos benefĂ­cios ofertados pela atividade fĂ­sica regular para os indivĂ­duos com AR, como a redução da dor, a melhora das condiçÔes gerais de vida, da qualidade do sono, das condiçÔes energĂ©ticas e do desempenho funcional, especialmente a longo prazo. 22 Os resultados evidenciados neste estudo concordam com outros achados na literatura. Myra et al (2015) realizaram um estudo de caso com um indivĂ­duo do gĂȘnero feminino com AR associada ao lĂșpus eritematoso sistĂȘmico, onde o submeteram a 15 sessĂ”es de cinesioterapia, duas vezes por semana.…”
Section: Discussionunclassified
“…While the reasons are not clearly documented, yoga may be less accessible and/or less acceptable to those from minority backgrounds (Middleton et al, 2013). However, the lack of minority participation in research is a historically documented phenomenon (Hussain Gambles, 2003; Ojha, 2008; Shavers Hornaday, Lynch, Burmeister, & Torner, 1997; Wendler et al, 2006).…”
Section: Case Studymentioning
confidence: 99%
“…However, the lack of minority participation in research is a historically documented phenomenon (Hussain Gambles, 2003; Ojha, 2008; Shavers Hornaday, Lynch, Burmeister, & Torner, 1997; Wendler et al, 2006). This pilot yoga study was designed specifically to examine the feasibility and acceptability of recruiting English- and Spanish-speaking minority patients receiving rheumatology care from a National Institutes of Health (NIH) Community Health Clinic located in the Washington, DC area (Middleton et al, 2013). A previous Health Behaviors and Health Beliefs study conducted within the same clinic population showed only 4.6% were using yoga for their arthritis symptoms (Middleton et al, 2013; Wallen et al, 2012).…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations